2013
DOI: 10.1186/1471-2164-14-39
|View full text |Cite
|
Sign up to set email alerts
|

Use of somatic mutations to quantify random contributions to mouse development

Abstract: BackgroundThe C. elegans cell fate map, in which the lineage of its approximately 1000 cells is visibly charted beginning from the zygote, represents a developmental biology milestone. Nematode development is invariant from one specimen to the next, whereas in mammals, aspects of development are probabilistic, and development exhibits variation between even genetically identical individuals. Consequently, a single defined cell fate map applicable to all individuals cannot exist.ResultsTo determine the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…This may be a reasonable assumption, although somatic mutations have been demonstrated in genome-wide surveys and are known to accumulate with age in mammals [328][329][330], but it is unclear how much they may contribute to normal phenotypic variation. For plants, where ample opportunity for somatic mutation exists and extensive research on genetic mosaicism has been conducted, Herrera [262] reviewed the available evidence and concluded that such genetic variation is only rarely responsible for appreciable portion of within-individual variation.…”
Section: The Central Argument: Fluctuating Asymmetry As a Measure Of mentioning
confidence: 99%
“…This may be a reasonable assumption, although somatic mutations have been demonstrated in genome-wide surveys and are known to accumulate with age in mammals [328][329][330], but it is unclear how much they may contribute to normal phenotypic variation. For plants, where ample opportunity for somatic mutation exists and extensive research on genetic mosaicism has been conducted, Herrera [262] reviewed the available evidence and concluded that such genetic variation is only rarely responsible for appreciable portion of within-individual variation.…”
Section: The Central Argument: Fluctuating Asymmetry As a Measure Of mentioning
confidence: 99%
“…Somatic mutations in normal cells from multicellular organisms can provide insights into the origins and past experiences of each cell 4 . The developmental lineages of individual cells may be reconstructed, as previously explored in studies using insertion/deletion mutations at short tandem repeats 1,5-11 (Supplementary Discussion A). Complete reconstruction of the bifurcating cell division tree requires at least one somatic mutation in the two daughter cells arising from each cell division.…”
mentioning
confidence: 99%
“…Analysis of poly-G repeats has successfully been used to study phylogenetic relationships between single cells in mouse development (22)(23)(24) and has been adapted for detecting preneoplastic clonal expansions in ulcerative colitis patients (25).…”
mentioning
confidence: 99%